AbÃ» Dzarr Al-Ghifari dan Perlawanan Ekonominya - Irfaan, Santosa (Al-Manahij: Jurnal Kajian Hukum Islam, 2009)
Abu Dzarr al-Ghifari has a unique character, especially in conveying has an opinion. He is one of the closest men to Muhammad Prophet, and his ideas are not only about tasawuf but also about other points, i.e economy.